2018
DOI: 10.1186/s12885-018-4585-1
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of RECQL is associated with poor prognosis in Chinese breast cancer patients

Abstract: BackgroundRECQL is a number of the RecQ DNA helicase family and plays an important role in maintaining genome stability. Although several studies have reported that RECQL mutations were correlated with the susceptibility to breast cancer, the effect on prognosis in breast cancer was not yet clarified. Here, we explored the association between RECQL expression level and survival in patients with breast cancer.MethodsIn the first cohort, the RECQL mRNA expression level was evaluated in 774 primary breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In a study by Arora et al low RECQL mRNA and protein levels in breast tumours were associated with poor breast cancer prognosis ( 1 ). This correlation was observed in a second study which showed low RECQL protein levels were correlated with poor survival (HR: 2.12, p-value: 0.015) ( 2 ). Furthermore, in a recent study, the cellular mechanism by which RECQL affects ER-positive cells was proposed, wherein RECQL in cooperation with FOXA1, directly regulates the expression of the ESR1 gene which encodes the ERα protein ( 28 ).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…In a study by Arora et al low RECQL mRNA and protein levels in breast tumours were associated with poor breast cancer prognosis ( 1 ). This correlation was observed in a second study which showed low RECQL protein levels were correlated with poor survival (HR: 2.12, p-value: 0.015) ( 2 ). Furthermore, in a recent study, the cellular mechanism by which RECQL affects ER-positive cells was proposed, wherein RECQL in cooperation with FOXA1, directly regulates the expression of the ESR1 gene which encodes the ERα protein ( 28 ).…”
Section: Introductionmentioning
confidence: 71%
“…The second study also observed that among 774 breast cancer patients, lower mRNA levels of RECQL were associated with poor distant recurrence-free survival (HR: 2.77, p-value <0.001) and disease-specific survival (HR: 3.10, p-value <0.001). In a cohort of 322 breast cancer patients, low RECQL protein levels correlated with poor survival (HR: 2.12, p-value: 0.015); however, the authors did not compare this association among ER-positive versus ER- individuals ( 2 ). These studies also showed that lower RECQL protein levels were associated with poor clinicopathological characteristics ( 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations